Identifikasi Faktor Pendukung dan Penghambat Keterlaksanaan Praktikum Biologi pada Sekolah Menengah Atas di Kecamatan Kaimana Kabupaten Kaimana - Sorry, Elsa Rosyana; Pagarra, Halifah; Ismail, Ismail (Biology Teaching and Learning, 2020)
Abstract. This study aimed to determine the supporting and inhibiting factors of the implementation of biology practicum in the senior high school in Kaimana Distcrit Kaimana Regency school year 2018/2019. This study was descriptive study. Sample in this study were the teachers in grade IX MIA SMA N 1 which is the class of experiment 1 and the teacher in grade IX MIA in SMA YPPK as the class of experiment 2. Data in this study was obtained by using purposive sampling technique. Data collection technique was done by questionnaire. Data in this study was analysed by using descriptive stastistical. The result of the study showed that (1) The level of implementation of Biology practice in SMA N 1 Kaimana is 77,78% and SMA YPPK is 33,33 %. (2) The major suporting factor such as laboratory is not available. (3) The obstacle that causes low percentage of practicum is the absence of laboratory room in school, the unavailability of laboratory tools and materials needed in practicum unit, there was no funds provided for practicum. (4) The efforts undertaken by school and teachers in handling this obstacle that is planning the implementation of practicum activities provided by the teachers in the lesson plan (RPP) as a form of teacher’s readiness, practicum funds provided by the teachers to purchase the practicum tools needed by school, laboratory management together by the teachers, and the teachers explain the materials as an effort to give understanding to students who do not participate in practicum activities. Keyword: Analysis, Biology Practicum, High School in Kaimana District